Musculoskeletal interventions of the spine for treating chronic scrotal pain: A scoping review - Switters, Jacob Marten; Wonka, Krista; Hohenauer, Erich (Journal of bodywork and movement therapies, 2025)
The aim of this scoping review is to identify and summarize the characteristics of subjects, interventions, outcomes, and evidence gaps in individuals with CSP who have undergone treatment using musculoskeletal interventions targeting the spine. PubMed, Cochrane Library, and ScienceDirect were searched, supplemented by reference list screening and pearl growing. Studies were included if they focused on spinal manipulations or mobilizations in individuals aged ≥18 years with CSP lasting ≥3 months and no specific underlying cause. Patient characteristics and interventions were systematically identified and synthesized. Ten articles met the eligibility criteria, including one case series and nine case studies, with a total of 50 subjects and no control group. The most frequently reported pain areas were the groin and thigh on the same side as the testicular pain. These symptoms can be aggravated by physical and sexual activity. Associated symptoms included sleep impairments, sexual dysfunction, and psychological disorders. All studies employed high-velocity, low-amplitude (HVLA) or mobilization techniques, primarily targeting the thoracolumbar junction, lumbar spine and sacroiliac joints. Outcomes were assessed in relation to pain, disability, quality of life, urinary symptoms, and sexual function with a follow-up of ≤8 months. The evidence for spinal musculoskeletal interventions for CSP is limited and weak. Subjects ranged in age from 32 to 39 years with pain duration from 4 months to 5 years. All articles used HVLA and/or mobilization of the spine with positive outcomes, however, it is impossible to say which intervention is most effective in reducing symptoms. •Evidence for spinal musculoskeletal interventions for CSP is limited and weak.•Sleep impairments, sexual dysfunction and psychological deficits are frequently reported.•Groin and thigh pain on the same side as the testicular pain is common.•CSP can be aggravated by physical and sexual activity.•Commonly used techniques are HVLA and manipulation of the TLJ, lumbar spine and SI joints.